Replication and ribosomal stress induced by targeting pyrimidine synthesis and cellular checkpoints suppress p53-deficient tumors - Hubackova, Sona; Davidova, Eliska; Boukalova, Stepana; Kovarova, Jaromira; Bajzikova, Martina; Coelho, Ana; Terp, Mikkel G; Ditzel, Henrik J; Rohlena, Jakub; Neuzil, Jiri (Cell death & disease, 2020)
p53-mutated tumors often exhibit increased resistance to standard chemotherapy and enhanced metastatic potential. Here we demonstrate that inhibition of dihydroorotate dehydrogenase (DHODH), a key enzyme of the de novo pyrimidine synthesis pathway, effectively decreases proliferation of cancer cells via induction of replication and ribosomal stress in a p53- and checkpoint kinase 1 (Chk1)-dependent manner. Mechanistically, a block in replication and ribosomal biogenesis result in p53 activation paralleled by accumulation of replication forks that activate the ataxia telangiectasia and Rad3-related kinase/Chk1 pathway, both of which lead to cell cycle arrest. Since in the absence of functional p53 the cell cycle arrest fully depends on Chk1, combined DHODH/Chk1 inhibition in p53-dysfunctional cancer cells induces aberrant cell cycle re-entry and erroneous mitosis, resulting in massive cell death. Combined DHODH/Chk1 inhibition effectively suppresses p53-mutated tumors and their metastasis, and therefore presents a promising therapeutic strategy for p53-mutated cancers.
Keywords: pyraziny; regulace genové exprese u nádorů; Oxidoreductases Acting on CH-CH Group Donors; Mice, Transgenic; Signal Transduction; oxidoreduktasy působící na CH-CH vazby; nádory prsu; Cell Proliferation; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; HCT116 Cells; Humans; Dihydroorotate Dehydrogenase; Mice, Inbred BALB C; Leflunomide; myši transgenní; Phenylurea Compounds; myši inbrední BALB C; zvířata; Pyrimidines; Breast Neoplasms; signální transdukce; myši inbrední NOD; Ribosomes; Protein Kinase Inhibitors; MFC-7 buňky; Tumor Suppressor Protein p53; Genes, erbB-2; proliferace buněk; checkpoint kinasa 1; Cell Cycle Checkpoints; fenylmočovinové sloučeniny; inhibitory proteinkinas; pyrimidiny; MCF-7 Cells; HCT116 buňky; nádorový supresorový protein p53; Gene Expression Regulation, Neoplastic; leflunomid; kontrolní body buněčného cyklu; ženské pohlaví; myši SCID; ribozomy; Animals; lidé; Mice, Inbred NOD; Mice, SCID; Checkpoint Kinase 1; geny erbB-2; dihydroorotátdehydrogenasa; Pyrazines; Female